A well-worn tallis for a new ceremony : trends in Israeli Haredi culture - Stadler, Nurit (Jewish identities in post modern society., 2012)
This text analyses the on-going reconstruction of Haredi culture in Israel, a process which has been spurred on by the challenges of modernity, the worldwide resurgence of religion, and the strong sway of Israeliness.